Ernest Hemingway in Slovenia since 1990 - Zupan, Simon (Acta neophilologica, 2020)
The article for the first time ever explores the recent non-fiction and poetry by the con-temporary Australian writer Krissy Kneen, who has Slovenian roots through her maternal grandmother. Kneen's writing, a literary tribute to her late grandmother Dragitca (Dragica Marušič), shows a desire to come to terms with her partly "Slovenian" gut microbiome and DNA, as she herself claims. They, in her view, along with the other elements in the process of identity formation, interestingly importantly help to constitute an ethnic iden-tity and, for that matter, any personal identity. This makes her writing very original within the extant diasporic literary production.
Keywords: American literature; ameriška književnost; book loans; Hemingway, Ernest; izposoja knjig; literarna kritika; literary criticism; literary reception; popkultura; popular culture; recepcija